The ultimate guide to Mac RAM. - Ion, Florence
Learn everything you need to know about how RAM works inside your Mac - and how to give your Mac a warp-speed boost by installing better, faster memory.
Keywords: Random access memory; Dual inline memory module (DIMM).; Fully Buffered DIMM; Small Outline DIMM; Virtual memory